The Impact of Distribution of (Qasida) System and One-Verse Union on The Imagery of Kurdish Classical Poetry - Khelil, Kameran I.; Mohammed, Abdi H.; Adak, Abdulrahman (Humanities Journal of University of Zakho, 2018)
Qasida as a form of poetry is overcome on Arabic and Persian Classical Poetry in Khorasani’s style which were cared and imitated by Eastern Islamic Poets. Accordingly, Critics and Poetry’s researchers and especially rhetoric scientists determined the rules, conceptions, and arts of composing poems based on ideal Qasida poem. After the end of Khorasani’s style and the weakness of Qasida’s form, Qasida was continued and its features with various figures were found in poetry even after the Mongolian attacks. Qasida’s system and unity of One-Line style are one of these characteristics. The Poet of a Qasida (Poem), based on the own Qasida System, divided his poetry into two or more main parts, according to the rules of One-Line style, tried to let the meaning of each line independent and has no relationship with another. Apparently, it is led to have a great impact on the poem even after its ending or weakness. The imitation and influence of the poem (Qasida) by Arabic-Islamic Poetical criticism are regarded to be the reasons behind the continuity of these characteristics. This phenomenon is stated differently in Kurdish Classical Poetry. Poets often divided their poems in to various topics and imageries where have no organic relationships with each other. They mostly tried to give a express an independent meaning in a verse without giving importance to the relations among all verses and lines in the whole poem. Therefore, it is probably clear that these characteristics as the division of Meanings of the poem and relying on the Verses Unity which the poetic experiences and Kurdish Classical unified-organic poetry are led to be doubted.